SGI quarterly. - Snoka Gakkai International; Soka Gakkai. Office of Informatin and Public Relations (Tokyo Soka Gakkai Office of Information and Public Relations, 1995)
Peace, culture, and education from a Buddhist perspective.
Title from cover.
Keywords: Snoka Gakkai -- Periodicals; Snoka Gakkai Buddhists -- Periodicals